A grid-net method to study the dynamic responses of steel-reinforced concrete target and projectile. Issue 2 (June 2017) - Xu, Weifang; Chen, Xiaowei; He, Liling; Zhang, Rong; Li, Huimin; Huang, Haiyin
In order to study the dynamic responses of a high-speed projectile striking into the steel-reinforced concrete target, a grid-net method has been developed in this article. The measuring system is composed of the grid nets fabricated by fine cables, light-emitting diode lamps, power supply systems, high-speed photography, and so on. Each grid net was pre-embedded along the rebar net. Multilayers of the grid nets were distributed with given space. The light-emitting diode lamp turns down when the cable is cut off. The status of the lamps is recorded by the high-speed photography. The basic idea is to trace the projectile by the on-off states of light-emitting diode lamps. In association with the high-speed photograph, the variation of the projectile velocity and the final depth of penetration could also be obtained. The depth of penetration value given by the grid measurement method was validated by the experimental result and the prediction of empirical formula and they show good agreement with each other.